2016
DOI: 10.1039/c5cp06796k
|View full text |Cite
|
Sign up to set email alerts
|

Metal free earth abundant elemental red phosphorus: a new class of visible light photocatalyst and photoelectrode materials

Abstract: Developing a high-performance photocatalyst and a photoelectrode with enhanced visible light harvesting properties is essential for practical visible light photocatalytic applications. Noble metal-free, highly visible light-active, elemental red phosphorus (RP) was prepared by a facile mechanical ball milling method, which is a reproducible, low cost and controllable synthesis process. The synthesis used inexpensive and abundant raw materials because most RP hybrids are based on expensive noble-metals. The nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 25 publications
1
38
0
1
Order By: Relevance
“…The fundamental absorption edge of the as-prepared and milled g-C 3 N 4 occurred at ~450 nm, which is the characteristic absorption wavelength of g-C 3 N 4 41 . The RPh-g-C 3 N 4 heterostructures showed significantly enhanced absorption in the visible region accompanied by a shift in the red absorption edge compared to the as-prepared P-g-C 3 N 4 and milled B-g-C 3 N 4 , which might be due to the combined synergistic effects of the narrow band gap and light harvesting characteristics of RPh and g-C 3 N 4 6 22 42 . These results indicate that the RPh-g-C 3 N 4 heterostructure is active in the wide visible light range and may produce photoinduced charge carriers under visible light photoirradiation, which is highly favorable for the photocatalytic reactions.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The fundamental absorption edge of the as-prepared and milled g-C 3 N 4 occurred at ~450 nm, which is the characteristic absorption wavelength of g-C 3 N 4 41 . The RPh-g-C 3 N 4 heterostructures showed significantly enhanced absorption in the visible region accompanied by a shift in the red absorption edge compared to the as-prepared P-g-C 3 N 4 and milled B-g-C 3 N 4 , which might be due to the combined synergistic effects of the narrow band gap and light harvesting characteristics of RPh and g-C 3 N 4 6 22 42 . These results indicate that the RPh-g-C 3 N 4 heterostructure is active in the wide visible light range and may produce photoinduced charge carriers under visible light photoirradiation, which is highly favorable for the photocatalytic reactions.…”
Section: Resultsmentioning
confidence: 96%
“…The direct photolysis of the organic pollutant was also performed under illumination conditions and the result showed that the negligible photolysis had occurred42. Figures 4a,b and S6 presents the photodegradation ability of P-g-C 3 N 4 , B-g-C 3 N 4 , 1-RPh-g-C 3 N 4 , 2-RPh-g-C 3 N 4 , 3-RPh-g-C 3 N 4 , and 4-RPh-g-C 3 N 4 heterostructured photocatalysts for the degradation of RhB and MO as a function of the irradiation time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Other semiconductors have lower bandgaps and a good match with the spectrum of sunlight, but their alignment of the valence band (VB) and conduction band (CB) is unfavorable for specific electrochemical reactions like the oxygen and hydrogen evolution reaction that are fundamental for photocatalytic water splitting. 2 Thus, the ability to optimize absorption spectra and finely manipulate band alignments in photoactive materials is critical to our future energy and environmental needs.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
“…Key words: red phosphorus; bentonite; adsorption enrichment-localized photodegradation; photocatalyst 半导体辅助光降解有机污染物是一种经济、环 保的环境污染治理方案, 受到了广泛关注。近年来, 研究发现硒、硫、红磷(RP)等单质半导体材料的带 隙窄、可见光响应强, 在光催化领域有着极大的应 用潜力。其中, RP 在可见光照射下不仅可以分解水, 还能降解污染物, 并且在地壳中储存丰富, 因此是 一种很有前景的元素半导体光催化剂 [1][2][3][4] 。RP 的禁 带宽度约为 1.7 eV, 吸收带边位置达到 680 nm, 是 一种典型的对可见光响应的 P 型半导体材料 [1] , 被 列为收集太阳能用于环境净化和制备清洁能源最有 前景的光催化剂之一。 此外, 通过控制 RP 晶体的形 貌 [5][6][7] 和晶面 [8] , 或者与其它材料复合, 可以进一步 提高 RP 的光催化活性。其中, 已报道的与 RP 成功 复合的材料有 CdS [9] 、MoS 2 [10][11] 、YPO 4 [2] 、TiO 2 [12] 、 C 3 N 4 [3,[13][14] 、黑磷 [4] 以及石墨烯 [15] 、还原氧化石墨烯 [11] 等。 然而, 上述材料或较难制备或制备成本高, 复合 催化剂难以进行大规模生产。因此, 寻找一种低成 本、 易获得, 并能进一步增强 RP 光催化性能的材料 具有十分重要的意义。 膨润土具有成本低、易获得、环境友好等优点, 是各种光催化剂的理想负载材料。膨润土是蒙脱石 的工业名称, 是一种黏土岩, 由 2 : 1 的堆叠层组成, 两层四面体片夹着八面体片, 具有膨胀现象 [16] 。在 硅氧四面体中 Al 3+ 对 Si 4+ 的同晶取代和铝氧八面体 中 Al 3+ 对 Mg 2+ 或 Zn 2+ 的同晶取代导致网状黏土表面 产生负电荷 [17] 。与其它黏土相比, 膨润土具有优异 的吸附能力, 在其层间、外部表面和边缘具有丰富 的吸附/交换活性位点 [18] 。因此, 膨润土是去除染料 的最有效吸附剂 [19] 。许多研究还表明, 膨润土是合 成具有较高光催化活性的复合光催化剂的良好载体, 例如 TiO 2 /膨润土 [20][21] 、ZnO/膨润土 [22] 、Bi 2 O 3 /膨润 土 [23] 、g-C 3 N 4 /Ag 3 PO 4 /膨润土 [24] 、BiVO 4 /膨润土 [25] 和 Ni 2 O 3 /膨润土 [26]…”
unclassified